Pemanfaatan Dana Desa dalam Prespektif Ekonomi Pembangunan Islam - Rudi Wijaya, Muhamad; Habibi Ritonga , Anas (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
With the Village Fund, the village government is required to manage village funds effectively. What is meant is the extent to which the targets (quantity, quality, and time) have been achieved by the village government in the utilization of village funds. The Village Fund is prioritized to finance development expenditures and empower village communities. The development in question is the construction of physical facilities and infrastructure such as roads, bridges, reservoirs and so on. In the view of Islamic economics, the main capital of economic development is human resources who work with noble character, honesty, intelligence, hard work and innovation. The Islamic view of economic development is focused on (a) the benefit of mankind from extinction; (b) human resources (good HR, reflecting Halal Income Sources (SPH); (c) protecting and maintaining natural ecosystems from damage; (d) maximizing land use and paying taxes to the state.